Current status of maternal mortality in hospitals in Peru - Távara, Luis (2015)
OBJECTIVE: To update rate and causes of maternal death at Peruvian hospitals. DESIGN: A Self Evaluation Manual was elaborated and 31 hospitals were selected 7 in Lima and Callao and 24 in the different regions of Peru. The Self Evaluation Manual was previously sent to the hospitals and a report was requested. A technical team had scheduled visits to each hospital and met with the board of directors. Registry information of the three previous years was obtained and processed with the V2, 6 Fox Pro Program. RESULTS: Seventeen hospitals to the coast, 10 to the mountains and 4 to the jungles; 25 were from the Ministry of Health, 3 from the Peruvian Institute of Social Security, 2 were integrated hospitals with origin in both institutions and 1 was aprivate hospítal. Previous year total deliveries were 100 063; 66,6% wíth 1 or moreprenatal controls; only 43,6% had had 4 or more controls; there were 20,5% cesareansection and 2,2% instrumental deliveries; 15,4% abortions, 6,7% low weight newborn babies and 4,3% low Apgar newborns. There were 349 maternal deaths in 155 797 live newborn delivered during the three years before the survey, with a rate of 224,04 per thousand live newborns. Lima’s rate was 120,14 and in the rest of the country it was 255,66. Coast hospitals rate was 147,11, in the mountains 145,36 and in the jungles 728,00. Integrated hospitals presented a higher rate and the rate was higher in the smallest and largest hospitals. Direct causes were responsible of 84,5% of deaths and indirect causes of 15,5%. Among direct causes, hemorrhage was the most frequent, followed by pregnancy induced hypertension. CONCLUSION:Maternal mortality rate continues being high in Peruvian hospitals and hemorrhage is the most important cause.